METODE DAN STRATEGI PENERJEMAHAN ISTILAH-ISTILAH PRAGMATIK DALAM BUKU “PRAGMATICS” KARYA GEORGE YULE KE DALAM BAHASA INDONESIA - Cipto Wardoyo (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2016)
This study tries to explain methods and strategies in translating pragmatic terms were used by translators in translating pragmatic terms. Source of data in this study was the book written by George Yule entitled “Pragmatics” (1996) which was translated into Indonesian language by Fajar Indah Wahyuni (2014).The writer in this research used the theory of translation method by Newmark (1988) and translation strategies by Vinay & Dalbernet (2000) and Baker (1992). The results of this study shows that the most dominant translation method was literal translation, it was 72 % from the total data, faithful translation method was 10%, semantic translation was 10%, free translation method was 5%, and communicative translation method was 3%. Moreover, strategies of translating pragmatic terms in the book